Managing Mining Risk Using Ore Reserve Estimates - Odertey, Felix (2012)
A Thesis submitted to the Institute of Distance Learning, Kwame Nkrumah University of Science and Technology, Kumasi in partial fulfillment of the requirements for the degree of Master of Science in Industrial Mathematics